10. SFPM workgroup report: "New techniques and quality assurance in brachytherapy". (December 2017) - Dejean, C.; Courrech, F.; Di Bartolo, C.; Ferre, M.; Gassa, F.; Pierrat, N.; Trafi, M.
Abstract : Introduction: Brachytherapy is a well-known treatment technique which delivers a high dose to a tumorous volume yet reducing irradiation for healthy surrounding tissue. Recent developments regarding the use of imaging highlighted the necessity to update and to complete the SFPM n°11 report of 1995 which used to be only about Iridium 192 high dose rate technique. This new report deals with techniques associated to a source projector for any dose rate (high dose rate HDR or pulsed PDR) and permanent Iodine 125 implants. Methods: Propositions are based on tests proposed by the SFPM, IAEA, GEC-ESTRO, AAPM, constructor guidelines, a recent bibliographic study and French users experience. Results: The report deals with: Source calibration presenting iridium 192 (most commonly used), Iodine 125 (non-available in French primary laboratory), Cobalt 60 ( still in development) Different kinds of imaging used for implantation or planning: ultrasound (US), scan (CT), MRI. More particularly, specific tests concerning US are presented due to their use for needles, applicators or sources implantation. Treatment planning: proposed tests concern mainly algorithms based on TG43 formalism but also new algorithms. Tests are divided into three groups: generic tests common to all techniques, specific tests dealing with treatments delivered by source projectors (HDR or PDR), specific tests concerning permanent implants. Quality assurance of the source projector is detailed according to HDR/PDR specificities for any radioelement used. Conclusions: These guidelines allow defining necessary tests from the implementation of a new technique to the current use. Each test is associated to a frequency and a level of action yet remaining suitable as a matter of clinical routine.